Bacterial Isolates and Antibiotic Sensitivity among Gambian Children with Severe Acute Malnutrition - Uduak A. Okomo; Danlami Garba; Augustin E. Fombah; Ousman Secka; Usman N. A. Ikumapayi; Jacob. J. Udo; Martin O. C. Ota (International Journal of Pediatrics)
Background. Establishing the pattern of infection and antimicrobial sensitivities in the local environment is critical to rational use of antibiotics and the development of management algorithms. Methods. Morbidity history and physical examination of 140 children with severe acute malnutrition were recorded. Their blood, stool, and urine samples were cultured and antibiotic sensitivity patterns determined for any bacterial pathogens isolated. Results. Thirty-eight children had a pathogen isolated from blood culture, 60% of which were considered contaminants. Coagulase negative staphylococcus was the predominant contaminant, while the major causes of bacteraemia were nontyphoidal Salmonella (13%), S. pneumoniae (10%), and E. coli (8%). E. coli accounted for 58% of the urinary isolates. No pathogen was isolated from stool. In vitro sensitivity by disk diffusion showed that 87.5% of the isolates were sensitive to ampicillin and/or gentamicin and 84.4% (27/32) to penicillin and/or gentamicin. Conclusions. A combination of ampicillin and gentamicin provides adequate antibiotic cover for severely malnourished children in The Gambia.